2021
DOI: 10.1186/s12866-021-02129-x
|View full text |Cite
|
Sign up to set email alerts
|

The infant gut resistome is associated with E. coli and early-life exposures

Abstract: Background The human gut microbiome harbors a collection of bacterial antimicrobial resistance genes (ARGs) known as the resistome. The factors associated with establishment of the resistome in early life are not well understood. We investigated the early-life exposures and taxonomic signatures associated with resistome development over the first year of life in a large, prospective cohort in the United States. Shotgun metagenomic sequencing was used to profile both microbial composition and AR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 62 publications
16
44
0
Order By: Relevance
“…Negative control yields were too low to quantify at 2 µl. Extracted DNA was amplified from all samples were prepared for sequencing on the NextSeq platform (shotgun metagenomics) using 150 nt paired end reads at the Marine Biological Laboratory (MBL) in Woods Hole, MA using established methods and as previously published 23 – 25 , 28 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative control yields were too low to quantify at 2 µl. Extracted DNA was amplified from all samples were prepared for sequencing on the NextSeq platform (shotgun metagenomics) using 150 nt paired end reads at the Marine Biological Laboratory (MBL) in Woods Hole, MA using established methods and as previously published 23 – 25 , 28 .…”
Section: Methodsmentioning
confidence: 99%
“…This was directly examined in our prospective analyses by assessing child growth between 0 and 2 years of age. Based on the DAG, the potential confounders (i.e., related to our exposure and outcome directly or hypothesized to be based on previously identified indirect associations in separate studies) to adjust for in our analyses were age (measured by age in days of the saliva sample), sex (male or female) 24 , 41 , delivery mode (vaginal or cesarean delivery) 3 , gestational age (age in weeks) 27 , 28 and diet (age when child started to eat solid foods in months) 41 . Although previous studies have found associations between maternal BMI or weight gain and children’s BMI 73 , literature identifying associations between maternal BMI and the child’s saliva microbiome have not found associations 41 , 74 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagenomics has been broadly applied for the study of the resistome of the human and animal microbiome ( Afridi et al, 2020 , 2021 ; Caselli et al, 2020 ), and of that from different habitats, including agricultural and urban soils ( Crofts et al, 2017 ). It has also been applied for local and international AMR surveillance of specific strains, mostly associated with HAI onset, such as carbapenem and quinolone-resistance Gram-negative bacteria, multi-resistant S. aureus and Enterobacterales , and M. tuberculosis ( Soliman et al, 2020 ; Lebeaux et al, 2021 ; Vazquez-Lopez et al, 2021 ; Waddington et al, 2022 ). Interestingly, by using a metagenomic approach, it was possible to show that more confined and cleaned environments had reduced microbial diversity and increased resistance, suggesting the implementation of strategies to restore bacterial diversity in certain built environments ( Mahnert et al, 2019 ).…”
Section: The Deep-sequencing Approach: Ngs and Wgsmentioning
confidence: 99%
“…children at 2-5 years [32] . Beyond gut microbiota, some studies have also been published showing differences in the infant oral microbiota due to maternal intrapartum antibiotics [33,34] .…”
Section: Impact Of Iap On the Developing Microbiota Compositionmentioning
confidence: 99%